Problem assessment: a case study of catfish culture in Mymensingh district, Bangladesh (Research in Agriculture Livestock and Fisheries, 2021)
The objectives of this study was to assess the extent of problems faced by the farmers in catfish culture with randomly selected 120 catfish cultivars in Trishal upazila under Mymensingh district. A structured questionnaire was used to collect data. Based on the level of problem faced by the farmers in catfish culture they were divided into three groups; less problem, moderate problem and high problem and it was observed through survey that the majority (60 %) of the farmers faced moderate problem while 22.50% percent of the farmers faced low problem and 17.50% farmer faced high problem. Farmers’ problem face was influenced by their media contact for fish farming, training exposure, level of education and organizational participation. Farmers having higher media contact, higher training participation, higher educational level and higher organizational involvement faced lower problem in catfish culture. On the basis of Problem Faced Index (PFI) score calculated to rank the problems, it was observed that high price of feed ranked most severe problem followed by unavailability of quality feed, high price of vaccine and medicine and low production and lack of local market. The findings may contribute in formulating policies to reduce farmers’ problem in catfish culture.Res. Agric., Livest. Fish.8(2): 241-248, August 2021